A Reexamination of the Value of Tax Options - Dammon, Robert M.; Dunn, Kenneth B.; Spatt, Chester S. (Review of Financial Studies, 1989)
This article reexamines the value of tax trading when the tax rate on long-term realizations is less than that on short-term realizations. In particular, the value of the option to realize long-term capital gains and repurchase stock in order to increase one’s tax basis and restart the option to realize future losses short term is examined empirically. Our estimate of the incremental value of restarting, which is based on the results of simulations of several alternative tax trading policies over a large number of independent return sequences, is generally much smaller than that reported by Constantinides (1984). The incremental value of restarting is shown to depend critically on the particular pattern of realized returns and the assumed tax treatment of unrealized capital gains at the end of the simulation period. The effects of stock price volatility, transaction costs, portfolio offset rules, and realization cutoff levels on the value of tax trading are also investigated.